Construção e validação de um instrumento para a implementação do processo de enfermagem em escolares hospitalizados - Marques, Daniela Karina Antao (2015)
Introduction: When providing care, the nurse needs to establish goals with the aim of meeting the needs of the child/family in a comprehensive way, in the biological, emotional, psychological, social and spiritual context, offering quality and visibility of the provided care. Objective: To construct an instrument for the implementation of the nursing process to hospitalized school-age children in the light of the Theory of Basic Human Needs. Method: This is a methodological study for the construction of an instrument for application of nursing process, which was held in the Pediatric Clinic of HULW/UFPB and developed in six steps: 1) identification of empirical indicators of Basic Human Needs in hospitalized school-age children; 2) Validation of indicators; 3) Formatting of nursing history and evaluation of the instrument by nurses who work in this field; 4) Development of wordings of diagnoses/ results and nursing interventions from the identified and validated clinical indicators; 5) Formatting of instrument for the planning of nursing care; and 6) Validation of the instrument for the planning of nursing care with nurses experts in ICNP®, assistants and teachers who work in Pediatric Clinic HULW/UFPB. The study was approved according to the Protocol nº 0654/13 and CAAE nº 24193313500005188. Results and discussion: In Step 1 it was classified the Basic Human Needs for hospitalized school-age children; evaluated five studies in HULW/UFPB that have validated indicators for pediatric customers and analyzed two instruments used for children aged 0-5 and teenagers according to the i-NMDS. This resulted in the elaboration, in Version 1, of the instrument, containing 301 indicators. In Step 2, we made the validation of 288 indicators for the assistant nurses and teachers. In Step 3, we performed the formatting and evaluation of the Version 2 of the instrument, being approved in its entirety. In Step 4, we developed 76 wordings of diagnoses/results and 135 nursing interventions from the validated indicators. In Step 5, we formatted the second part of the instrument based on the model used in Pediatric Clinic, in order to use it in the phases of diagnosis, planning, implementation and evaluation of nursing care. Finally, in Step 6, we performed the validation of the instrument for the planning of nursing care with nursing workers experts in ICNP®, who validated 49 wordings of nursing diagnoses/results and 77 nursing interventions. The instrument was reorganized and presented to be validated by nurses, who have approved it in its entirety. The instrument for the implementation of the nursing process in hospitalized school-age children was elaborated in four pages: two correspond to the nursing history, applied in the phase of data collection, and the other two pages contain the wordings of diagnoses/results and nursing interventions that may contribute for application of the other phases of the nursing process. Final considerations: We hope that the research results may contribute to the implementation of the nursing process for hospitalized school-age children, besides bringing reflections and enhancements of nursing care.